2015
DOI: 10.1371/journal.pone.0127600
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide Reductase Subunit M2 Predicts Survival in Subgroups of Patients with Non-Small Cell Lung Carcinoma: Effects of Gender and Smoking Status

Abstract: BackgroundRibonucleotide reductase catalyzes the conversion of ribonucleotide diphosphates to deoxyribonucleotide diphosphates. The functional enzyme consists of two subunits - one large (RRM1) and one small (RRM2 or RRM2b) subunit. Expression levels of each subunit have been implicated in prognostic outcomes in several different types of cancers.Experimental DesignImmunohistochemistry for RRM1 and RRM2 was performed on a lung cancer tissue microarray (TMA) and analyzed. 326 patients from the microarray were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Human RR is composed of three known subunits, RRM1 (large subunit), RRM2 (small subunit) and an encoded P53-controlled ribonucleotide reductase (P53R2) that are differentially regulated during the cell cycle2930. R1 protein concentrations are relatively constant throughout the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Human RR is composed of three known subunits, RRM1 (large subunit), RRM2 (small subunit) and an encoded P53-controlled ribonucleotide reductase (P53R2) that are differentially regulated during the cell cycle2930. R1 protein concentrations are relatively constant throughout the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…RRM2 is often overexpressed in many kinds of cancers, such as colorectal cancer, non-small cell lung cancer (NSCLC), breast cancer, bladder cancer, ovarian cancer, pancreatic cancer, head and neck cancer and lung cancer [12][13][14][15][16]. RRM2 also can be considered as a prognostic marker for cancers including NSCLC, cervical cancer, and pancreatic cancer [17][18][19]. Additionally, RRM2 is associated with chemo-resistance during cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1A. It has been demonstrated that high RRM2 expression is an indicator of poor prognosis in many types of cancer [17][18][19][33][34][35]. Here, we analyzed the relationship between RRM2 expression and the survival of GBM patients.…”
Section: Rrm2 Expression Is Enhanced In Human Glioma Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analyses would be needed to clarify this issue. RRM2 is a ribonucleotide reductase which participates in DNA repair, invasion and proliferation and has been related to poor lung cancer prognosis 46. SLC2A1 is a glucose receptor (also named GLUT1) involved in the uptake of glucose by mammalian cells 47.…”
Section: Discussionmentioning
confidence: 99%